Implementation of Family Planning Policy through Male Operation Method (MOP) in Widodomartani Vilage, Sleman Regency 2024 - Aeni, Nur; Mahendra, Gerry Katon (Journal of Social and Policy Issues, 2025)
This study aims to analyze the implementation of the Family Planning (KB) program through the Male Operation Method (MOP) in Widodomartani Village, Sleman Regency in 2024. Using the theoretical framework of Edward III and Grindle, the research employed a qualitative descriptive approach with data obtained through observation, interviews, and documentation. The findings reveal that program implementation has been systematically carried out through planning, socialization, registration, service delivery, and evaluation. Various strategies were used, including formal meetings, door-to-door approaches, involvement of Male Family Planning Groups, and the use of social media platforms such as YouTube. In terms of resources, both funding and medical personnel support were adequate. Nevertheless, male participation remained low, with a declining number of participants between 2022 and 2024. Contributing factors include social stigma, misconceptions about MOP, and limited participant quotas. Additionally, cultural perceptions such as the assumption that men undergoing MOP are more likely to engage in extramarital affairs also hinder participation. On the other hand, socialization targeting women proved more effective, as mothers play a decisive role in family planning decisions. The study concludes that improving MOP effectiveness requires comprehensive education for men, inclusive communication strategies for couples, and stronger support from health workers and community leaders to eliminate negative stigma.